A fog-like structure titanium oxide coated SiC / C composite nanofiber, a preparation method and application thereof
Patent Information
- Application Number
- CN202611368493.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-23
AI Technical Summary
公告号为CN106978652B的中国专利申请,虽涉及TiO2纤维,但未涉及其氢化处理及吸波应用
本发明公开的一种类雾凇结构氢化氧化钛包覆SiC/C复合纳米纤维的制备方法,将SiC/C纤维提前分散在无水乙醇,将TiO2-F127单胶束先溶解于无水乙醇再加入,通过调控反应过程中的甘油用量调节TiO2单胶束的包覆层厚度。通过胶束自组装工艺制备出类雾凇结构TiO2包覆SiC/C复合纳米纤维前驱体,再离心干燥及后续氢化处理获得具有优异吸波性能的类雾凇结构的TiO2-x包覆SiC/C复合纳米纤维。本发明方法工艺简单,制备的复合纳米纤维形貌完整,类雾凇结构TiO2-x包覆在SiC/C纤维表面,同时表现出优异的吸波性能。SiC/C纳米纤维的一维结构呈相互交织排布的空间形态,该构型为内部导电网络的搭建提供了天然优势,不仅能够降低电子在单根纤维内部的传输阻力,还可加速电子在不同纤维之间的跨纤维跃迁,进而实现电导损耗效率的显著提升。含TiO2单胶束的引入,在SiC/C纤维表面包覆含类雾凇结构TiO2。氢化处理后,引入大量氧空位,且在TiO2-x纳米晶粒表面形成的有序/无序层,构筑起多级界面体系,进而显著提高其电磁波吸收性能。通过此方法制备的纳米复合纤维在电磁波吸收方面具有广阔的应用前景。
Smart Images

Figure CN122960012A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing material preparation technology, specifically relating to a rime-like structure of hydrogenated titanium oxide coated SiC / C composite nanofibers, its preparation method, and its application. Background Technology
[0002] The rapid development of modern electronic information technology, especially the introduction of fifth-generation wireless communication systems, has ushered in an era of the Internet of Things. On the one hand, people enjoy the various conveniences brought by 5G; on the other hand, the resulting electromagnetic radiation permeates every corner of our lives. Therefore, developing high-performance absorbing materials to rapidly and efficiently attenuate electromagnetic waves has significant economic and strategic value. Simultaneously, the new development situation has also placed new demands on the electromagnetic wave absorption performance of absorbing materials. On the one hand, absorbing materials must possess strong electromagnetic wave attenuation capabilities and a wide electromagnetic wave absorption bandwidth to ensure that incident electromagnetic waves can be rapidly attenuated and lost. On the other hand, absorbing materials should also be lightweight and thin to adapt to the trend of lightweighting and miniaturization in electronic equipment and weaponry.
[0003] In the field of microwave absorbing materials, one-dimensional SiC / C nanofibers have attracted widespread attention due to their high strength, good chemical stability, and ability to construct internal conductive networks. However, the surface structure of pure SiC / C nanofibers is monolithic, which cannot further enhance the multiple scattering and polarization loss of electromagnetic waves. Chinese patent application CN113737314B prepared flexible SiC / C nanocomposite fibers through electrospinning and high-temperature pyrolysis, and modified their dielectric properties by doping with transition metals (such as molybdenum) to improve electromagnetic wave absorption. As a promising functional oxide, titanium dioxide (TiO₂) is also being explored. 2-x Due to its superior properties, TiO2 has attracted widespread research attention in catalysis, energy storage, and dielectric materials. The oxygen vacancies and ordered / disordered interfaces in its crystal lattice have been shown to significantly enhance dipole polarization and interfacial polarization, making it a promising microwave absorber. While Chinese patent application CN106978652B relates to TiO2 fibers, it does not cover their hydrogenation treatment or microwave absorption applications. The hydrogenated TiO2... 2-x This will create oxygen vacancies and ordered / disordered interfaces in the crystal lattice, significantly enhancing dipole polarization and interfacial polarization, thus making TiO₂... 2-x The complex permittivity of TiO2 was significantly improved, enhancing the electromagnetic wave absorption performance of the material and thus strengthening its application potential in the field of microwave absorption. Based on this significant discovery, TiO2... 2-x TiO2 has been considered a potential candidate material for microwave absorbers. Currently, the preparation of TiO2... 2-xThere are numerous methods for coating various materials. Among them, micellar self-assembly, as a bottom-up preparation strategy, is mainly driven by intermolecular forces. This assembly process can usually be carried out spontaneously under mild ambient pressure. This method can effectively construct composite materials with regular morphologies.
[0004] Therefore, there is an urgent need to find a way to utilize TiO2. 2-x By introducing a SiC / C nanofiber system and designing a reasonable interface structure, the electromagnetic wave absorption performance of SiC / C nanofibers can be further improved, with the aim of preparing lightweight, haze-like structure hydrogenated titanium oxide-coated SiC / C composite nanofibers with excellent wave absorption properties. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, the present invention aims to provide a haze-like structure hydrogenated titanium oxide-coated SiC / C composite nanofiber, its preparation method, and its application, in order to solve the technical problem of how to construct a haze-like structure hydrogenated titanium oxide coating layer on the surface of SiC / C nanofibers, introduce multi-level heterogeneous interfaces and oxygen vacancy defects, thereby synergistically improving the polarization loss capability and electromagnetic wave absorption performance of the composite fiber.
[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure, comprising: SiC / C nanofibers were dispersed in anhydrous ethanol, and titanium-containing block copolymer micelles and glycerol were added to carry out a micelle self-assembly reaction to obtain a mixed solution of SiC / C composite nanofibers coated with TiO2 containing a rime-like structure. After cooling, centrifugation, washing, and drying, a precursor of TiO2 coated with SiC / C composite nanofibers with a rime-like structure was obtained. Subsequently, hydrogenation treatment was carried out in a reducing atmosphere to obtain hydrogenated titanium oxide coated with SiC / C composite nanofibers with a rime-like structure.
[0007] Preferably, the SiC / C nanofibers are prepared by electrospinning; the titanium-containing block copolymer micelles are TiO2-F127 single micelles; the TiO2-F127 single micelles are first dissolved in anhydrous ethanol and then added to anhydrous ethanol in which SiC / C nanofibers are dispersed.
[0008] More preferably, the ratio of SiC / C nanofibers, TiO2-F127 single micelles, glycerol and anhydrous ethanol is (0.05~0.1) g : (3~5) g : (5~10) mL : 15 mL.
[0009] Preferably, in the SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure, the thickness of the hydrogenated titanium oxide coating layer is 3~5 nm.
[0010] Preferably, the conditions for the micelle self-assembly reaction include: stirring the reaction at an oil bath temperature of 80~120°C for 6~10 hours.
[0011] Preferably, centrifugal washing is performed using anhydrous ethanol; drying conditions include drying at 60-80°C for 10-15 hours.
[0012] Preferably, the heating rate of the hydrogenation treatment is 2~5°C / min, the treatment temperature is 600~800°C, and the holding time is 1~4h.
[0013] Preferably, the reducing atmosphere is a mixture of Ar and H2, wherein the volume content of H2 is 10%.
[0014] The present invention also discloses a haze-like structure hydrogenated titanium oxide coated SiC / C composite nanofiber, which is prepared by the above-mentioned method for preparing haze-like structure hydrogenated titanium oxide coated SiC / C composite nanofiber.
[0015] The present invention also discloses the application of the above-mentioned haze-like structure hydrogenated titanium oxide coated SiC / C composite nanofibers in electromagnetic wave absorption.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing SiC / C composite nanofibers with a haze-like structure using hydrogenated titanium dioxide. The method involves pre-dispersing SiC / C fibers in anhydrous ethanol, dissolving TiO2-F127 single micelles in anhydrous ethanol before adding them, and adjusting the coating thickness of the TiO2 single micelles by controlling the amount of glycerol used during the reaction process. A haze-like structure TiO2-coated SiC / C composite nanofiber precursor is prepared using a micelle self-assembly process. This precursor is then centrifuged, dried, and subsequently hydrogenated to obtain a haze-like structure TiO2 nanofiber with excellent microwave absorption properties. 2-x SiC / C composite nanofibers are coated. The method of this invention is simple, and the prepared composite nanofibers have complete morphology, exhibiting a frost-like TiO₂ structure. 2-x Coated on the surface of SiC / C fibers, it exhibits excellent microwave absorption properties. The one-dimensional structure of SiC / C nanofibers is an interwoven spatial arrangement, which provides a natural advantage for building an internal conductive network. This not only reduces the transmission resistance of electrons within a single fiber but also accelerates the transfiber transition of electrons between different fibers, thereby significantly improving the conductivity loss efficiency. The introduction of TiO2-containing single micelles coats the surface of SiC / C fibers with TiO2 containing a frost-like structure. After hydrogenation treatment, a large number of oxygen vacancies are introduced, and in the TiO2... 2-xThe ordered / disordered layers formed on the surface of nanocrystals construct a multi-level interface system, thereby significantly improving their electromagnetic wave absorption performance. Nanocomposite fibers prepared by this method have broad application prospects in electromagnetic wave absorption.
[0017] Furthermore, the mass-to-volume ratio of SiC / C nanofibers:TiO2-F127 single micelles:glycerol:anhydrous ethanol is (0.05~0.1) g:(3~5) g:(5~10) mL:15 mL, which ensures that SiC / C serves as the matrix fiber, and also introduces TiO2-containing single micelles into its structural design. Since the TiO2-containing single micelle precursor is easily hydrolyzed, anhydrous ethanol is chosen as the solvent to ensure the full reaction between SiC / C nanofibers and TiO2-F127 single micelles.
[0018] Furthermore, in order to control the thickness of the coating layer containing TiO2 micelles, the glycerol content should not be too high or too low, so as to ensure that the TiO2 layer of the frost-like structure monomer is neither too thin nor too thick.
[0019] Furthermore, in order to improve the contact between SiC / C nanofibers and TiO2-F127 single micelles, the reactants were placed in an oil bath environment at 80~120℃ to provide a certain thermal driving force to facilitate their full reaction.
[0020] Furthermore, in order to ensure that SiC / C nanofibers and TiO2-F127 single micelles react fully, it is essential to stir for a sufficient period of time to allow for complete reaction and avoid problems such as uneven coating and incomplete reaction.
[0021] Furthermore, sufficient centrifugation and washing cycles are required to ensure complete removal of glycerol from the solution, yielding a pure, rime-like TiO2-coated SiC / C composite nanofiber precursor.
[0022] Furthermore, to ensure that the residual anhydrous ethanol after centrifugation is completely evaporated, it is placed in a forced-air drying oven at 60~80℃ for 10~15 hours to allow the residual solvent to fully evaporate, facilitating subsequent high-temperature heat treatment.
[0023] Furthermore, a large number of oxygen vacancies were introduced by hydrogenating the TiO2-coated SiC / C nanocomposite fiber precursor with a rime-like structure under an Ar / H2 (10%) atmosphere, and then... 2-x Ordered / disordered layers form on the surface of nanocrystals, while TiO2... 2-x Uniform coating forms a heterogeneous interface on the fiber surface, constructing a multi-level interface system. Regarding the fiber's firing temperature, the heating rate must be within a certain range; if the temperature rises too quickly, the fiber morphology will be difficult to maintain. Excessively high sintering temperatures will cause fiber breakage, so the temperature must be appropriate.
[0024] This invention discloses a haze-like structure of hydrogenated titanium oxide-coated SiC / C composite nanofibers, which combines the advantages of the internal conductive network of one-dimensional SiC / C fibers with the haze-like morphology of surface hydrogenated titanium oxide. This results in a multi-level heterogeneous interface, high-density oxygen vacancy defects, and an ordered / disordered layer structure, significantly enhancing multiple mechanisms of dipole polarization, interfacial polarization, and conductivity loss, while maintaining the fiber's flexibility and lightweight properties. This makes it a high-performance electromagnetic wave absorbing material. As a microwave absorbing material, it can construct an internal conductive network, introduce oxygen vacancies to increase internal defects, and form ordered / disordered multi-layered heterogeneous interfaces, thereby exhibiting an increase in both the real and imaginary parts of the dielectric constant, enhanced reflection loss, and a significantly improved effective absorption width.
[0025] When the haze-like structure of hydrogenated titanium oxide coated SiC / C composite nanofibers of the present invention is used as an electromagnetic wave absorbing material, it can achieve wide-band effective coverage of Ku-band, X-band and even C-band with a relatively thin thickness, and has strong reflection loss capability. It effectively solves the problems of narrow absorption bandwidth and single loss mechanism of existing wave absorbing materials, and provides an ideal material for the preparation of advanced electromagnetic wave absorbing devices that are strong, wide, light and thin. Attached Figure Description
[0026] Figure 1 Different TiO₂ prepared in Examples 2 and 4 of this invention 2-x SEM images of the coated composite nanofibers; where (a) is SiC / C@TiO 2-x (a) SEM image of the nanofibers, representing an addition of 6 mL of glycerol; (b) SiC / C@TiO 2-x SEM image of -2 nanofibers, representing an addition of 7 mL of glycerol; Figure 2 The EPR comparison diagrams of composite nanofibers prepared in Examples 1 and 2 of this invention with and without hydrogenation treatment are shown. Figure 3 The three-dimensional reflection loss diagrams are shown for the composite nanofibers prepared in Examples 1 and 2 of this invention as microwave absorbing materials; wherein, (a) is the three-dimensional reflection loss diagram of SiC / C@TiO2 nanofibers; (b) is the three-dimensional reflection loss diagram of SiC / C@TiO2 nanofibers. 2-x Three-dimensional reflection loss diagram of nanofibers; Figure 4 The hoarfrost-like structure TiO2 prepared in Example 2 of this invention 2-x Effective absorption width of SiC / C composite nanofibers at different thicknesses. Detailed Implementation
[0027] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.
[0029] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.
[0030] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.
[0031] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.
[0032] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.
[0033] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.
[0034] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.
[0035] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.
[0036] This invention provides a haze-like structure of hydrogenated titanium oxide (TiO2). 2-x This paper discusses the preparation and application of SiC / C composite nanofibers, highlighting the easily achievable and simple preparation conditions. The main techniques employed are simple micellar self-assembly and hydrogenation to obtain TiO₂ nanofibers with a frost-like structure and excellent electromagnetic wave absorption properties. 2-xSiC / C composite nanofibers were coated. SiC / C fibers were pre-dispersed in anhydrous ethanol. TiO2-F127 single micelles were dissolved in anhydrous ethanol and then added. Glycerol was added to adjust the coating thickness of the TiO2 single micelles. Glycerol acts as a confinement agent and stabilizer during TiO2 nucleation and growth. High-viscosity glycerol encapsulates the F127 / TiO2 composite single micelles through strong hydrogen bonds, increasing steric hindrance and limiting free collisions and multilayer stacking between micelles, thereby controlling the coating thickness of the TiO2 single micelles on the fiber surface. The resulting solution was magnetically stirred in an oil bath to obtain a mixed solution containing a frost-like structure TiO2 coated with SiC / C composite nanofibers. The reacted solution was cooled to room temperature, centrifuged, dried, and subsequently hydrogenated to obtain a frost-like structure TiO2 with excellent microwave absorption properties. 2-x Coating SiC / C composite nanofibers. Incorporating a frost-like structure of TiO2. 2-x Dielectric samples were prepared by mixing SiC / C composite nanofibers with paraffin in a certain proportion, and their electromagnetic wave absorption properties were tested; TiO2... 2-x The introduction of TiO2 not only effectively improves the structural stability of SiC / C, but also significantly broadens the effective absorption width of the composite fibers through oxygen vacancy defects and ordered / disordered interface design. This invention is the first to combine TiO2-F127 single micelles with SiC / C nanofibers, preparing a hoarfrost-like TiO2 structure with excellent electromagnetic wave absorption performance through micelle self-assembly and hydrogenation processes. 2-x SiC / C composite nanofibers coated.
[0037] The present invention provides a method for preparing SiC / C composite nanofibers with a haze-like structure coated with hydrogenated titanium oxide, comprising the following steps: S1. The SiC / C nanofibers prepared by electrospinning are uniformly dispersed in anhydrous ethanol in advance. TiO2-F127 single micelles are dissolved in anhydrous ethanol and then added. A certain amount of glycerol is added to adjust the coating thickness of the TiO2 single micelles. The mass-to-volume ratio of SiC / C nanofibers:TiO2-F127 single micelles:glycerol:anhydrous ethanol was (0.05~0.1) g:(3~5) g:(5~10) mL:15 mL; the prepared rime-like structure hydrogenated titanium oxide coated SiC / C composite nanofibers with TiO2 was... 2-x The coating thickness is approximately 3-5 nm. The coating thickness is determined by... Figure 1 The scanned images of the samples obtained with different amounts of glycerol added and the corresponding scale measurements give a range.
[0038] A method for preparing SiC / C nanofibers by electrospinning includes: First, dissolving 0.5 g of PCS and 0.6 g of PVP in a solvent consisting of 7 mL of THF and 3 mL of DMF, and stirring for 0.5 h to ensure complete dissolution. Then, mixing the two solutions and stirring at room temperature for 24 h yields a stable and transparent spinning solution. Next, transferring the spinning solution into a 10 mL plastic syringe equipped with a stainless steel needle with an inner diameter of 0.33 mm, using aluminum foil as a collector. The high voltage for electrospinning is set to 16 kV, and the solution is fed to the needle at a constant rate of 2.4 mL / h, with a distance of 16 cm between the collector and the needle. Subsequently, the spun fibers are collected on the aluminum foil and placed in an oven for non-melting solidification at 100 °C for 2 h, followed by further treatment at 200 °C for 2 h, thereby obtaining pre-oxidized nanofibers. The pre-oxidized nanofibers were then placed in an argon atmosphere and calcined at 1250 °C for 2 h at a heating rate of 2.5 °C / min to obtain SiC / C nanofibers.
[0039] The preparation method of TiO2-F127 single micelles includes: firstly, adding 1.5 g of triblock copolymer Pluronic F127 to 30.0 mL of tetrahydrofuran (THF) solution and stirring until completely dissolved; then, slowly adding 2.4 mL of acetic acid (HOAc) and 3.2 mL of hydrochloric acid (HCl) dropwise to the above mixed solution and stirring continuously for 10 min to prepare a homogeneous and transparent mixed solution; next, adding 3.0 mL of tetrabutyl titanate (TBOT) dropwise to the solution and stirring rapidly for 10 min to obtain a yellowish-white mixed solution; finally, transferring the obtained solution to two volumetric flasks, placing them in a sealed drying oven, and evaporating at 45 ℃ for 30 h to finally obtain TiO2-F127 single micelles.
[0040] S2. The obtained solution was magnetically stirred at an oil bath temperature of 80~120℃ for 6~10h to obtain a mixed solution of SiC / C composite nanofibers coated with TiO2 containing a rime-like structure. S3. Cool the reaction solution to room temperature and wash it with anhydrous ethanol by centrifugation to remove residual glycerol from the solution; place the pure solute obtained by centrifugation in an oven and dry it at a temperature of 60~80℃ for 10~15h to obtain a pure rime-like structure TiO2-coated SiC / C composite nanofiber precursor. S4. The SiC / C composite nanofiber precursor with a frost-like structure TiO2 coated with SiC / C composite nanofiber obtained in step S3 is hydrogenated in an Ar / H2 (10%) atmosphere, heated to 600-800°C at a rate of 2-5°C / min, and annealed for 1-4 hours to obtain a frost-like structure TiO2.2-x SiC / C composite nanofibers coated.
[0041] The hoarfrost-like TiO2 structure prepared by this invention 2-x The SiC / C composite nanofibers coated with SiC not only possess the excellent environmental resistance of silicon carbide, but also exhibit the high specific surface area, high aspect ratio, and frost-like structure of nanofibers in TiO2. 2-x The introduction of this technology has enabled the formation of multilayer heterogeneous interfaces, such as oxygen vacancy defects and ordered / disordered interfaces.
[0042] Pure silicon carbide fibers have relatively low real and imaginary dielectric constant values, are mainly characterized by dielectric loss, and exhibit a narrow effective absorption width and low loss capability. TiO₂ 2-x The introduction of this material generates oxygen vacancy defects and multilayered heterogeneous interfaces of ordered / disordered structures, which synergize with SiC / C nanofibers, resulting in a significant improvement in both effective absorption width and optimal reflection loss. (This is followed by an unrelated sentence about a hoarfrost-like TiO2 structure.) 2-x The SiC / C composite nanofibers have a simple preparation method and promising microwave absorption properties, and have certain application prospects.
[0043] Another technical solution of the present invention is a hoarfrost-like TiO₂ structure. 2-x Application of SiC / C composite nanofibers in electromagnetic wave absorption.
[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0045] Example 1 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.05g of SiC / C fiber, then disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Meanwhile, 4g of TiO2-F127 single micelles were weighed and dissolved in 5mL of anhydrous ethanol. This solution was stirred under magnetic stirring for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask. Under magnetic stirring, slowly add solution B to solution A and stir magnetically for 10 minutes to allow it to react fully, thus obtaining solution C. Next, 6 mL of glycerol was measured and slowly added to solution C under magnetic stirring to obtain reaction solution D; Then, the round-bottom flask containing reaction solution D was connected to a condenser and placed in an oil bath at 100°C for self-assembly, with a reaction time of 6 hours. After centrifuging the obtained reactants, they were dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The obtained nanofibers were then collected and sintered in an Ar atmosphere, heated at 2°C / min, and annealed at 700°C for 4 hours to obtain TiO2-coated SiC / C composite nanofibers with a frost-like structure.
[0046] The surface of SiC / C nanofibers is coated with TiO2 with a frost-like structure, while maintaining the one-dimensional morphology of the nanofibers. Since no hydrogenation treatment is performed, the final product is a TiO2-coated SiC / C composite nanofiber with a frost-like structure.
[0047] Example 2 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.05g of SiC / C fiber, then disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Meanwhile, 4g of TiO2-F127 single micelles were weighed and dissolved in 5mL of anhydrous ethanol. This solution was stirred under magnetic stirring for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask. Under magnetic stirring, slowly add solution B to solution A and stir magnetically for 10 minutes to allow it to react fully, thus obtaining solution C. Next, 6 mL of glycerol was measured and slowly added to solution C under magnetic stirring to obtain reaction solution D; Then, the round-bottom flask containing reaction solution D was connected to a condenser and placed in an oil bath at 100°C for self-assembly, with a reaction time of 6 hours. After centrifuging the obtained reactants, they were dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The obtained nanofibers were then collected and sintered in an Ar / H2 atmosphere, heated at 2°C / min, and annealed at 700°C for 4 hours to obtain a frost-like TiO2 structure. 2-x SiC / C composite nanofibers coated.
[0048] Since all parameters except the sintering atmosphere remained unchanged during the reaction, the morphology of the fibers remained almost unchanged, and the overall structure remained similar to frost. TiO₂ 2-x The formation of this increases both the real and imaginary parts of the system's dielectric constant.
[0049] Example 3 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.05g of SiC / C fiber, then disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Meanwhile, 5g of TiO2-F127 single micelles were weighed and dissolved in 5mL of anhydrous ethanol. This solution was stirred under magnetic stirring for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask. Under magnetic stirring, slowly add solution B to solution A and stir magnetically for 10 minutes to allow it to react fully, thus obtaining solution C. Next, 6 mL of glycerol was measured and slowly added to solution C under magnetic stirring to obtain reaction solution D; Then, the round-bottom flask containing reaction solution D was connected to a condenser and placed in an oil bath at 100°C for self-assembly, with a reaction time of 6 hours. After centrifuging the obtained reactants, they were dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The obtained nanofibers were then collected and sintered in an Ar / H2 atmosphere, heated at 2°C / min, and annealed at 600°C for 4 hours to obtain TiO2 with a frost-like structure. 2-x SiC / C composite nanofibers coated.
[0050] Increasing the amount of TiO2-F127 single micelles can improve the coating amount. Because of the increased content of added TiO2-F127 single micelles, the TiO2 coating on the surface of SiC / C fibers is more effective. 2-x increase.
[0051] Example 4 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.05g of SiC / C fiber, then disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Meanwhile, 4g of TiO2-F127 single micelles were weighed and dissolved in 5mL of anhydrous ethanol. This solution was stirred under magnetic stirring for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask. Under magnetic stirring, slowly add solution B to solution A and stir magnetically for 10 minutes to allow it to react fully, thus obtaining solution C. Next, 7 mL of glycerol was measured and slowly added to solution C under magnetic stirring to obtain reaction solution D; Then, the round-bottom flask containing reaction solution D was connected to a condenser and placed in an oil bath at 100°C for self-assembly, with a reaction time of 6 hours. After centrifuging the obtained reactants, they were dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The obtained nanofibers were then collected and sintered in an Ar / H2 atmosphere, with the temperature increased at 2°C / min, and annealed at 700°C for 4 hours to obtain TiO2 with a frost-like structure. 2-x SiC / C composite nanofibers coated.
[0052] As the amount of glycerol added increases, its steric hindrance effect will be significantly enhanced, thus the TiO2 coating on the surface of SiC / C fibers will be affected. 2-x less.
[0053] Example 5 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.05g of SiC / C fiber, then disperse it in 5mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Meanwhile, 4g of TiO2-F127 single micelles were weighed and dissolved in 5mL of anhydrous ethanol. This solution was stirred under magnetic stirring for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask. Under magnetic stirring, slowly add solution B to solution A and stir magnetically for 10 minutes to allow it to react fully, thus obtaining solution C. Next, 6 mL of glycerol was measured and slowly added to solution C under magnetic stirring to obtain reaction solution D; Then, the round-bottom flask containing reaction solution D was connected to a condenser and placed in an oil bath at 100°C for self-assembly, with a reaction time of 6 hours. After centrifuging the obtained reactants, they were dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The obtained nanofibers were then collected and sintered in an Ar / H2 atmosphere, heated at 2°C / min, and annealed at 600°C for 4 hours to obtain TiO2 with a frost-like structure. 2-x SiC / C composite nanofibers coated.
[0054] It is evident that compared to sintering at 700°C, the crystallinity is significantly reduced, which is detrimental to TiO₂. 2-x Crystallization.
[0055] Example 6 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.1g of SiC / C fiber (obtained by electrospinning), disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Weigh 3g of TiO2-F127 single micelles and dissolve them in 5mL of anhydrous ethanol. Stir magnetically for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask, slowly add solution B while stirring magnetically, and stir for 10 minutes to obtain solution C; Measure 5 mL of glycerol and slowly add it to solution C to obtain reaction solution D (total anhydrous ethanol 15 mL). After connecting the round-bottom flask to the condenser, place it in an 80°C oil bath for a self-assembly reaction for 10 hours. After the reactants were cooled, they were washed three times by centrifugation with anhydrous ethanol and dried in an oven at 80°C for 15 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The precursor fibers were heated to 800℃ at 5℃ / min and held for 1h in an Ar / H2 atmosphere to obtain SiC / C composite nanofibers with hydrogenated titanium oxide coating and a frost-like structure, with a coating thickness of 3nm.
[0056] Example 7 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.075g of SiC / C fiber (obtained by electrospinning), disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Weigh 4g of TiO2-F127 single micelles and dissolve them in 5mL of anhydrous ethanol. Stir magnetically for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask, slowly add solution B while stirring magnetically, and stir for 10 minutes to obtain solution C; Measure 8 mL of glycerol and slowly add it to solution C to obtain reaction solution D (total anhydrous ethanol 15 mL). After connecting the round-bottom flask to the condenser, place it in a 120°C oil bath for self-assembly reaction for 8 hours; After the reactants were cooled, they were washed three times by centrifugation with anhydrous ethanol and dried in an oven at 70°C for 12 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The precursor fibers were heated to 650℃ at 3.5℃ / min and held for 2h in an Ar / H2 atmosphere to obtain SiC / C composite nanofibers with hydrogenated titanium oxide coating and a rime-like structure, with a coating thickness of 4.5nm.
[0057] Example 8 A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure includes the following steps: Weigh 0.1g of SiC / C fiber (obtained by electrospinning), disperse it in 10mL of anhydrous ethanol, and let it stand for a period of time to allow it to disperse fully, thus obtaining solution A; Weigh 5g of TiO2-F127 single micelles and dissolve them in 5mL of anhydrous ethanol. Stir magnetically for 0.5h to obtain a homogeneous solution B. Pour solution A into a round-bottom flask, slowly add solution B while stirring magnetically, and stir for 10 minutes to obtain solution C; Measure 5 mL of glycerol and slowly add it to solution C to obtain reaction solution D (total anhydrous ethanol 15 mL). After connecting the round-bottom flask to the condenser, place it in a 100°C oil bath for a self-assembly reaction for 10 hours. After the reactants were cooled, they were washed three times by centrifugation with anhydrous ethanol and dried in an oven at 60°C for 10 hours to obtain a TiO2-coated SiC / C composite nanofiber precursor with a rime-like structure. The precursor fibers were heated to 600℃ at 2℃ / min and held for 3h in an Ar / H2 atmosphere to obtain SiC / C composite nanofibers with hydrogenated titanium oxide coating and a frost-like structure, with a coating thickness of 5nm.
[0058] Figure 1 Different TiO₂ prepared in Examples 2 and 4 of this invention 2-x SEM images of the coated composite nanofibers; where (a) is SiC / C@TiO 2-x (a) SEM image of the nanofibers, representing an addition of 6 mL of glycerol; (b) SiC / C@TiO 2-x The SEM image of the -2 nanofibers represents an addition of 7 mL of glycerol. The image shows that when the glycerol addition is 6 mL, the TiO₂ coating on the SiC / C fiber surface... 2-xThe nanoparticles are dense and uniform, forming a distinct haze-like structure with a coating thickness of approximately 4-5 nm. However, when the glycerol content increases to 7 mL, the number of coated particles on the fiber surface significantly decreases and their distribution becomes sparse, resulting in a thinner coating. This indicates that glycerol acts as a confinement agent and stabilizer during self-assembly, increasing steric hindrance through strong hydrogen bonding, effectively suppressing the multilayer stacking of TiO2 single micelles on the fiber surface, thereby achieving precise control over the coating amount.
[0059] Figure 2 The figures show a comparison of the EPR (Enhanced Permeability) of the composite nanofibers prepared in Examples 1 and 2 of this invention with and without hydrogenation treatment. As can be seen from the figures, the unhydrogenated sample exhibits only a very weak EPR signal, while the hydrogenated sample shows a significantly enhanced symmetrical single-peak signal at a g-factor of approximately 2.004. This signal is attributed to the resonant absorption of single electrons trapped by oxygen vacancies. This indicates that hydrogenation treatment successfully introduced a large number of oxygen vacancy defects into the TiO2 lattice, providing sufficient defect active sites for subsequent enhancement of dipole polarization.
[0060] Figure 3 The three-dimensional reflection loss diagrams are shown for the composite nanofibers prepared in Examples 1 and 2 of this invention as microwave absorbing materials; wherein, (a) is the three-dimensional reflection loss diagram of SiC / C@TiO2 nanofibers; (b) is the three-dimensional reflection loss diagram of SiC / C@TiO2 nanofibers. 2-x Three-dimensional reflection loss diagram of nanofibers; as can be seen from the figure, the minimum reflection loss of the unhydrogenated sample is only about -20.42 dB, and the effective absorption area is relatively narrow; while the minimum reflection loss of the hydrogenated sample (Figure b) is significantly enhanced to over -50.77 dB, and the valley region in the three-dimensional diagram is significantly widened, covering a wider frequency and thickness range. This indicates that the oxygen vacancies introduced by hydrogenation and TiO2... 2-x The ordered / disordered layers formed on the surface of nanocrystals, together with SiC / C fibers, construct a multi-level heterogeneous interface, which synergistically enhances interface polarization and dipole polarization, significantly improving electromagnetic wave absorption capability.
[0061] Figure 4 The hoarfrost-like structure TiO2 prepared in Example 2 of this invention 2-x Effective absorption width of SiC / C composite nanofibers at different thicknesses; please refer to [link / reference]. Figure 4 As can be seen, the obtained TiO₂ has a rime-like structure 2-x Coating SiC / C composite nanofibers significantly improves the effective absorption width, achieving full coverage of the Ku and X bands, as well as most of the C band coverage, at different thicknesses.
[0062] In summary, this invention discloses a rime-like structure hydrogenated titanium oxide-coated SiC / C composite nanofiber, its preparation method, and its application. Using SiC / C nanofibers prepared by electrospinning and TiO2-F127 single micelles as raw materials, and anhydrous ethanol as a solvent, TiO2 is prepared using micelle self-assembly and hydrogenation processes. 2-x Coating SiC / C nanocomposite fibers. The process is simple, and the prepared fibers have a unique frost-like structure. By controlling the amount of glycerol used in the reaction process, TiO2 coating on the surface of SiC / C nanofibers can be achieved. 2-x Precise control of coating amount. Hydrogenation treatment introduces a large number of oxygen vacancies, which are then deposited in TiO2. 2-x Ordered / disordered layers form on the surface of nanocrystals, while TiO2... 2-x Uniformly coated on the fiber surface to form a heterogeneous interface, constructing a multi-level interface system, promoting the formation of a frost-like TiO2 structure. 2-x SiC / C composite nanofibers exhibit excellent electromagnetic wave absorption. Using SiC / C nanofibers as a matrix, TiO2-F127 single micelles were selectively added for self-assembly. The resulting composite nanofiber precursor was then hydrogenated, which not only maintained the one-dimensional SiC / C fiber structure but also generated more oxygen vacancy defects and ordered / disordered multilayer heterogeneous interfaces, improving the real and imaginary parts of the dielectric constant and introducing multiple loss mechanisms to achieve optimal impedance matching and electromagnetic loss. The application of micelle self-assembly and hydrogenation processes directly prepared frost-like TiO2 structures. 2-x SiC / C composite nanofibers are coated with TiO2. 2-x It shares advantages with SiC / C nanofibers. High-performance microwave absorbing materials can be prepared using a simple process.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide in a rime-like structure, characterized in that, include: SiC / C nanofibers were dispersed in anhydrous ethanol, and titanium-containing block copolymer micelles and glycerol were added to carry out micelle self-assembly reaction to obtain a mixed solution of SiC / C composite nanofibers coated with TiO2 containing a rime-like structure. After cooling, centrifugation, washing, and drying, a precursor of SiC / C composite nanofibers with a rime-like structure of TiO2 was obtained; subsequently, hydrogenation treatment was carried out in a reducing atmosphere to obtain SiC / C composite nanofibers with a rime-like structure of hydrogenated titanium oxide.
2. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 1, characterized in that, The SiC / C nanofibers were prepared by electrospinning. The titanium-containing block copolymer micelles are TiO2-F127 single micelles; the TiO2-F127 single micelles are first dissolved in anhydrous ethanol and then added to anhydrous ethanol containing dispersed SiC / C nanofibers.
3. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 2, characterized in that, The ratio of SiC / C nanofibers, TiO2-F127 single micelles, glycerol and anhydrous ethanol is (0.05~0.1) g : (3~5) g : (5~10) mL : 15 mL.
4. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 1, characterized in that, In the haze-like structure of hydrogenated titanium oxide-coated SiC / C composite nanofibers, the thickness of the hydrogenated titanium oxide coating layer is 3~5 nm.
5. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 1, characterized in that, The conditions for the micelle self-assembly reaction include: stirring the reaction at an oil bath temperature of 80~120°C for 6~10 hours.
6. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 1, characterized in that, The centrifugal washing is performed using anhydrous ethanol; the drying conditions include drying at 60-80°C for 10-15 hours.
7. The method for preparing SiC / C composite nanofibers with a haze-like structure coated with hydrogenated titanium oxide according to claim 1, characterized in that, The heating rate of the hydrogenation treatment is 2~5°C / min, the treatment temperature is 600~800°C, and the holding time is 1~4h.
8. The method for preparing SiC / C composite nanofibers coated with hydrogenated titanium oxide with a rime-like structure according to claim 1, characterized in that, The reducing atmosphere is a mixture of Ar and H2; wherein the volume content of H2 is 10%.
9. A type of haze-like structure hydrogenated titanium oxide coated SiC / C composite nanofibers, characterized in that, The SiC / C composite nanofibers were prepared using the method described in any one of claims 1-8 for the preparation of hydrogenated titanium oxide-coated nanofibers with a rime-like structure.
10. The application of the haze-like structure hydrogenated titanium oxide-coated SiC / C composite nanofibers as described in claim 9 in electromagnetic wave absorption.
Citation Information
Patent Citations
A method for preparing a poly(titanium acetate) precursor sol-spinning solution and a titanium dioxide nanofiber photocatalyst.
CN106978652B
A flexible SiC / C nanocomposite fiber, its preparation method and application
CN113737314B